Two systems of symbolic writing : the Indus script and the Easter Island script - Richter-Ushanas, Egbert ([Traugott Bautz], 2012)
The author and the book The deciphering of the Indus-script with recourse to the R̥g-Veda shows that the Indus-culture is older than the Vedic canon that was transmitted orally. The Yoga has the same origin as it can be deduced from Indus seals and tablets with a person sitting in a yoga-posture. This is also evident through the Yoga practice of the greeting of the sun, where the hands form the Indus-sign for the sun. Since the Indus cities were destroyed in a relatively early time the Indus-script was conserved as a word script. It did not develop into a letter-script as the Egyptian writing.